Capital budgeting analysis and government tax incentives intervention of paddy non-granary area in Peninsular Malaysia - Roslan Azman; Masoumeh Hosseinpour; Mohd Mansor Ismail; Ilmas Abdurofi; Bashir Hamman Gabdo (Universitas Gadjah Mada, 2025)
Rice has been a staple food in Malaysia. Besides, paddy is among the food crop sub sector which has always been as an especial core attention for the government. The present study evaluates the capital budgeting and investigates the effect on Government tax incentives to the project assessment of paddy industry in non-granary areas. Financial appraisal of Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) and Payback Period (PP) are the selected indicators in capital budgeting approach. According to the results, paddy projects in nongranary area is financially viable where all financial indicators provide lucrative values. The project may be sustained with the proper profitability even though the distortion of revenue and costs are existed during the project. Since the project drags potential assessment in terms of financial appraisal, the more attention is suggested for the government to encourage the non-granary area to be part of paddy concern in Malaysia.